2008
DOI: 10.1021/ef800057n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Model Molecules Resembling Asphaltene-Like Structures in Aqueous Organic Solvent Systems

Abstract: Molecular dynamics (MD) simulations were used to study the aggregation of model molecules representing some structural features of asphaltenes in different solvents, namely, water, toluene, and heptane. Three different model molecules with similar molecular weights were developed as representatives of continental- and archipelago-type structures of asphaltenes. Two types of continental models were employed, one containing no charged entities and another containing one anionic terminal carboxylic group on an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
190
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 38 publications
18
190
0
Order By: Relevance
“…This means that key factor(s) ruling asphaltene self-association has (have) not been identified yet. MD study started by comparing the aggregation properties in water, toluene, and heptane of three different model molecules after 10 ns 25 . The molecules were found to selfassociate in single pure solvents by stacking of their polyaromatic rings.…”
Section: Adsorption At Liquid/liquid Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that key factor(s) ruling asphaltene self-association has (have) not been identified yet. MD study started by comparing the aggregation properties in water, toluene, and heptane of three different model molecules after 10 ns 25 . The molecules were found to selfassociate in single pure solvents by stacking of their polyaromatic rings.…”
Section: Adsorption At Liquid/liquid Interfacesmentioning
confidence: 99%
“…The molecules studied were chosen to represent different models proposed to represent common structural and compositional aspects of petroleum asphaltenes: continental model, archipelago model and anionic continental model [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharjee et al studied the asphaltene-like structures in aqueous/organic solvent systems. 33 The simulations showed that the model molecules tend to form aggregates in pure solvent, and specific fractions with ionic terminal groups on the aliphatic chains could dramatically enhance the interfacial activity of the entire asphaltene population. Such findings indicated that the interfacial activity of the asphaltene molecules was probably related to their terminal group characteristics rather than the polyaromatic rings.…”
Section: Introductionmentioning
confidence: 96%
“…Nano-aggregates in the correct size range (∼ 2 nm and above) formed without inhibitor, provided that the asphaltene side chains contained polar groups (with or without heteroatoms in the polyaromatic core). The nano-aggregates displayed internal π − π stacking of the polyaromatic rings [8,7,30]. Without the polar side chain groups, the aggregates were larger and above ∼ 4 nm (with heteroatoms) or non-existent (without heteroatoms).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the asphaltene polar groups are associated mainly to nitrogen, oxygen and sulphur that can be found in the polyaromatic ring structures (as heteroatoms) and in the side chains [7,8,9]. These groups enhance self-aggregation, precipitation and adsorption [10,11].…”
Section: Introductionmentioning
confidence: 99%